Impacts of Mn Content and Mass Loading on the Performance of Flexible Asymmetric Solid-State Supercapacitors Using Mixed-Phase MnO2/N-Containing Graphene Composites as Cathode Materials - Hsin-Ya Chiu; Chun-Pei Cho (C, 2023)
MnO2/nitrogen-containing graphene (x-NGM) composites with varying contents of Mn were used as the electrode materials for flexible asymmetric solid-state supercapacitors. The MnO2 was a two-phase mixture of γ- and α-MnO2. The combination of nitrogen-containing graphene and MnO2 improved reversible Faraday reactions and charge transfer. However, excessive MnO2 reduced conductivity, hindering ion diffusion and charge transfer. Overloading the electrode with active materials also negatively affected conductivity. Both the mass loading and MnO2 content were crucial to electrochemical performance. x-NGM composites served as cathode materials, while graphene acted as the anode material. Operating by two charge storage mechanisms enabled a synergistic effect, resulting in better charge storage purposes. Among the supercapacitors, the 3-NGM1//G1 exhibited the highest conductivity, efficient charge transfer, and superior capacitive characteristics. It showed a superior specific capacitance of 579 F·g−1, leading to high energy density and power density. Flexible solid-state supercapacitors using x-NGM composites demonstrated good cycle stability, with a high capacitance retention rate of 86.7% after 2000 bending cycles.